EVALUATION OF DRUG RELATED PROBLEMS (DRPS) ON THE USE ANTITUBERCULOSIS DRUGS IN PEDIATRIC PATIENTS AT FOUR COMMUNITY HEALTH CENTERS IN BANDUNG CITY - Evryandi Gultom, Edwin
Tuberculosis is a chronic infectious disease caused by the bacterium Mycobacterium tuberculosis. Evaluation of drug use is an activity to evaluate the use of drugs in a structured and continuous manner to ensure that the drugs used are indicated, effective, safe, and rational. Evaluation of drug use is used to determine problems related to treatment / Drug Related Problems (DRPs) and find appropriate solutions. DRPs are a form of pharmaceutical service that describes a situation where health professionals (pharmacists) assess the existence of treatment discrepancies in achieving real therapy. The purpose of this study was to look at the analysis of DRPs referring to the Pharmaceutical Care Network Europe Association (PCNE) classification in the use of OAT to achieve therapeutic success in pediatric patients as well as the correlation of the number of patients DRPs to demographic data. The research method used was descriptive observational with retrospective sampling. The sampling was based on patient medical record data from January 2022 – December 2022 and obtained a population of 117 patients. Based on the patient's treatment, the identified DRPs were untreated symptoms or indications (5.61%), potential adverse drug reactions (7.65%), no indication for the drug administered (3.06%), inappropriate drug combination/drug interaction (32.65%), duplication of treatment or improper active ingredient (0.51%), treatment duration too short (10.2%), treatment duration too long, (5.1%), incorrect dosing time instructions, unclear, or missed (27.55%), less drugs given (3.06%), over-administered drugs (4.59%). The results of statistical analysis of the number of DRP patients against demographic data showed that there were no significant differences between sex, family history, and TB category. Also, there was no correlation between the number of DRPs of patients with age (Correlation coefficient = 0.038) and body weight (Correlation coefficient = 0.043)